A Personalized Approach to the Treatment of Primary Open-Angle Glaucoma - A. L. Onishchenko; N. V. Maltseva; A. Sh. Smirnova; O. M. Kazantseva; S. I. Makogon (Oftalʹmologiâ)
Aim — to study of gene polymorphisms affecting the effectiveness of timolol treatment of primary open-angle glaucoma.Patients and Methods. The study included 39 Russian patients (29 women and 10 men) aged 53 to 89 years old with a diagnosis of primary open-angle glaucoma (POAG). Intraocular pressure (IOP) was measured before the start of therapy and after 2 weeks during treatment. Сoefficient of decrease in IOP was calculated in percentage of its initial level (∆D). Patients were genotyped according to the polymorphic loci MMP1-160insG, MMP12A-82G, TIMP1C536T, ADRB1Arg389Gly, ADRB1Ser49Gly, NAT2Lys268Arg, GSTP1Ile105Val using the corresponding SNP-express reagent kits (NPF Lytech, Moscow).Results. No effect of MMP12A-82G, TIMP1C536T, ADRB1Arg389Gly, NAT2Lys268Arg polymorphisms on efficiency of reduction of IOP under action of thymolol in “best” eyes was revealed. The carriage of a homozygous genotype GSTP1Ile105Ile resulted in the best ophthalmic hypotensive effect of a timolol (∆D ≥ 20 %), which probability was 5.63 times higher in comparison with ∆D < 20 %. In the “worst” eyes, the association of carriage of a combination of wild genotypes GSTP1Ile105Ile×NAT2Lys268Lys with the best response of patients to timolol was revealed. The ophthalmic hypotensive effect of 10 ≤ ∆D < 20 % in such carriers was more than 11 times more likely than ∆D < 10 %.Conclusion. The carriage of the wild genotype GSTP1Ile105Ile determines the best ophthalmic hypotensive effect of timolol and can be a prognostic marker for the effective treatment of patients with POAG. The combination of wild genotypes GSTP1Ile105Ile×NAT2Lys268Lys can contribute to the better therapeutic effect of timolol, and mutant ones can prevent it.